Political connection and tax avoidance on sharia stocks; good for business? - Fadlil Abdani (Al-Amwal : Jurnal Ekonomi dan Perbankan Syari'ah, 2020)
Abstract This research is used to determine the influence of political connections on tax avoidance. Researchers use government ownership and directors and commissioners who hold multiple positions as former government officials and military officials to measure variable political connections. Tax avoidance is measured using cash effective tax rate (CETR). The data in this study used secondary data in annual reports on companies included in the Jakarta Islamic Index period 2015-2018. The method used in this study is quantitative analysis, and the results show that political connections through government ownership affect tax avoidance; the same is also evident in political connections through BOD profiles and BOC profiles affecting tax avoidance.Keywords: Tax Avoidance, Political Connection, Sharia Stock